III. The Impact of Digital Economic Infrastructure Construction on the Development Level of Digital Economy in Countries Along the Belt and Road Initiative - Lam, Haocong (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
The global shift towards the digital economy necessitates accelerated development of digital infrastructure. Since the inception of the "Belt and Road" initiative, China and partner nations have significantly advanced economic cooperation. Mainly, with the introduction of the "Digital Silk Road" concept in 2017, nations along the initiative have actively pursued digital infrastructure projects. Through analysing domestic and international research, this article conducts an empirical analysis and assesses the impact of digital economic infrastructure on participating countries' digital economies. It is concluded that the level of digital economic infrastructure construction, such as mobile network coverage, fixed broadband penetration and complete Internet servers, can promote the development of the digital economy in these countries.